PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM (Studi Kasus pada Perusahaan Property & Realestate Sub Sektor Kontruksi dan Bangunan yang Terdaftar di Bursa Efek Indonesia) - Apriani, Rizki (Nusa Putra University, 2020)
This study is aimed at fulfilling college assignments and to understand how the influence of financial ratios on stock prices in construction and building sector real estate companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2019 period. By using financial ratios such as profitability, liquidity and solvency ratios. The financial ratios studied are Current Ratio (CR), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin (NPM), and Operating Profit Margin (OPM), as independent variables and stock prices as dependent variable. In this study we as researchers used as many as 8 samples of companies listed on the Indonesian stock exchange. The data used is quantitative data on annual financial statements of companies listed on the Indonesian stock exchange (IDX). This study uses multiple linear regression analysis using the SPSS program. The results of this research that we obtain show that the independent variable has a significant effect on the dependent variable.